Constructing Community Identity and Local Wisdom Content in Regional TV Stations Digital Broadcasting - Lopulalan, Dortje L. Y.; Salakay, Selvianus; Sopacua, Yustina; Alfredo, Ronald (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2022)
This study analyzes Net TV Ambon and Indosiar Ambon as media that broadcast and show local content. The TV station show material with added value to explore the local wisdom, highlight cultural identity, and maintain its existence entering the digital broadcasting era. This study uses the qualitative approach and descriptive data as analysis methods. Data collection from research subjects was carried out using purposive sampling techniques. Primary data, namely the main data in the study, was conducted through in-depth interviews with informants, specifically KPID Maluku, KSP TV Indosiar Ambon, Liaison Officer Net TV Ambon, and local PH (Production House) in Ambon. Secondary data is obtained through reviewed impressions and various libraries from related sources. The results revealed that: 1) Net TV Ambon and Indosiar Ambon have the jargon "local wisdom and its existence in maintaining and preserving the culture of “The Basudara People”. 2) TV Net Ambon and Indosiar Ambon catch opportunities from the digitalization of broadcasting to expand and develop broadcast services for the public. The Net TV Ambon and Indosiar Ambon develop the distribution of local content and various information on local wisdom in the Maluku region that can be watched widely throughout Indonesia and even globally.